In Aid We Trust : Hearts and Minds and the Pakistan Earthquake of 2005 - Andrabi, Tahir (The MIT Press, 2018)
In 2005 an earthquake in northern Pakistan led to a significant inflow of international relief groups. Four years later, trust in Europeans and Americans was markedly higher among those exposed to the earthquake and the relief that followed. These differences reflect the greater provision of foreign aid and foreigner presence in affected villages rather than preexisting population differences or a general impact of disasters on trust. We thus demonstrate large-scale, durable attitudinal change in a representative Muslim population. Trust in Westerners among Muslims is malleable and not a deeply rooted function of preferences or global (as opposed to local) policy and actions.